1974
DOI: 10.1128/aac.5.2.106
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Acetohydroxamic Acid and 12 Antibiotics Against 14 Gram-Negative Pathogenic Bacteria

Abstract: Acetohydroxamic acid (AHA) is a potent inhibitor of urease which prevents alkalinization of urine and stone formation in rats in the presence of infection caused by urease-producing bacteria. Because an antibacterial effect of AHA, and synergy between kanamycin and AHA have also been described, we studied the interaction between AHA and 12 antibiotics against 14 gram-negative bacteria. Synergy, sometimes to a striking degree, was found in 17% of interactions; however, antagonism was detected in 5%. Infecting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1974
1974
1990
1990

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Small-scale preparations of whole-cell DNA followed the protocol given below. A single colony from a fresh overnight growth on a urea-glucoseeosin Y-methylene blue agar plate was suspended in 500 ,ul of Tris hydrochloride at pH 8.0, 50 ,ul of 10-mg/ml lysozyme was added, and the sample was incubated at room temperature for 15 Cosmid cloning. Chromosomal DNA from E. coli 1021 was partially cleaved with the restriction endonuclease Sau3AI, sized on a sucrose gradient (10 to 40%), and ligated to the BamEII-digested and alkaline phosphatase-treated cosmid vector pREG153, a R388 derivative (8), as described elsewhere (10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small-scale preparations of whole-cell DNA followed the protocol given below. A single colony from a fresh overnight growth on a urea-glucoseeosin Y-methylene blue agar plate was suspended in 500 ,ul of Tris hydrochloride at pH 8.0, 50 ,ul of 10-mg/ml lysozyme was added, and the sample was incubated at room temperature for 15 Cosmid cloning. Chromosomal DNA from E. coli 1021 was partially cleaved with the restriction endonuclease Sau3AI, sized on a sucrose gradient (10 to 40%), and ligated to the BamEII-digested and alkaline phosphatase-treated cosmid vector pREG153, a R388 derivative (8), as described elsewhere (10).…”
Section: Methodsmentioning
confidence: 99%
“…When produced by bacteria that infect the urinary tract, urease is thought to play a role in virulence. Alkaline urine results from an increased concentration of ammonium ions, which can lead to renal tissue damage (14), struvite stone formation (1,5,14,21,24,25), enhanced attachment of the infecting bacteria to bladder transitional epithelium (17), and inactivation of antibiotics (15). There is evidence that urease-producing bacteria have a predilection for the urinary tract (9,26).…”
mentioning
confidence: 99%
“…(i) In contrast to the findings of others (2), we have previously shown that AHA has definite antibacterial effects (2b); these were demonstrated again in the present studies (Fig. 4 and 5). (ii) For reasons that remain obscure, but are unrelated to effects on pH, AHA may act synergistically or antagonistically with a variety of antibiotics against gram-negative urinary pathogens (4). In contrast, the potentiating effect of AHA for methenamine is directly related to its effect on pH (Fig.…”
Section: Resultsmentioning
confidence: 99%